The Role of Bone Marrow Cells and Peripheral Blood Cells in the Osteogenic Process - Vukelić-Nikolić Marija Đ.; Đorđević Ljubiša B. (Acta Veterinaria, 2024)
The osteogenic process is a complex and dynamic biological phenomenon essential for the initial formation of bones during embryonic development and the continuous remodeling and repair of bones throughout an individual’s life. It involves coordination of various cell types, signaling pathways, and environmental factors to ensure proper bone formation and maintenance. The main role in this process belongs to bone marrow cells and peripheral blood cells. This paper provides an overview of currently available literature data about different contributions of bone marrow cells and peripheral blood cells to the osteogenic process. Focusing on their differentiation, signaling pathways, and interactions within the bone microenvironment this article aims to provide a comprehensive understanding of how these cells orchestrate the osteogenic process, offering insights into their therapeutic potential. Understanding these complex cellular interactions is crucial for the development of advanced therapeutic approaches in regenerative medicine and orthopedics, which will ultimately improve outcomes in patients with bone defects and bone-related disorders.